1971
DOI: 10.1002/1097-0142(197102)27:2<247::aid-cncr2820270202>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Drug dosage and remission duration in childhood lymphocytic leukemia

Abstract: Children with acute lymphocytic leukemia in complete remission were randomized between 2 combination chemotherapy schedules for continuation of their remissions. One group received full dosage of 4 antileukemic drugs, and the other received half dosage of the same compounds. Median durations of complete remission and of hematologic remission were longer in the full‐dosage than half‐dosage group. Four out of 21 patients in the full‐dosage group continue in their initial complete remission for 40 to 48 months an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

1971
1971
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(55 citation statements)
references
References 8 publications
(3 reference statements)
0
54
0
1
Order By: Relevance
“…One of the earliest studies of dose response was made in childhood acute lymphoblastic leukaemia where Pinkel (1971) showed that remission duration was significantly prolonged (15 vs 6 months) in children given 'full' rather than 'half' doses of four drug maintainance therapy. However, in a larger study (van Eys, 1989) no difference in outcome was seen for the higher dose arm.…”
Section: Dose Escalating Studiesmentioning
confidence: 99%
“…One of the earliest studies of dose response was made in childhood acute lymphoblastic leukaemia where Pinkel (1971) showed that remission duration was significantly prolonged (15 vs 6 months) in children given 'full' rather than 'half' doses of four drug maintainance therapy. However, in a larger study (van Eys, 1989) no difference in outcome was seen for the higher dose arm.…”
Section: Dose Escalating Studiesmentioning
confidence: 99%
“…Studies 1-111 were the initial studies of combination chemotherapy and preventive craniospinal i r r a d i a t i~n .~,~ Study IV was designed to determine the need for maximumtolerated dosage of multiple chemotherapy agents and preventive CNS therapy was not given. 8 In Study V more aggressive preventive CNS therapy was first tried3 and this was tested in a controlled manner in Study VI.' Study VII compared the two forms of CNS prophylaxis employed in Studies V and VI and tested the value of periodic "reinduction" chemotherapy during remi~sion.~ The latter studies were subjected to detailed analysis more recently as welL9…”
Section: Therapymentioning
confidence: 99%
“…The large inter-individual differences in plasma concentration profiles after oral MT implies different intensity of therapy, and children with adverse pharmacokinetic parameters might lack hepatotoxicity and be at increased risk for relapse, due to reduced systemic drug exposure to both liver and lymphoblasts (Pinkel et al, 1971;Craft et al, 1981). In support of hepatotoxicity reflecting treatment intensity, we found a relation between mATMT and the rise in white cell counts following cessation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, patients with hepatoxicity seem to have delayed systemic clearance of MTX (Parker et al, 1980). If hepatotoxicity does reflect treatment intensity, reduction of the doses of MTX and 6MP for patients with abnormal liver function tests could carry an increased relapse risk (Pinkel et al, 1971), which was also indicated by the present study.…”
Section: Discussionmentioning
confidence: 99%